PENGEMBANGAN MEDIA PREZI MIND MAP UNTUK MENINGKATKAN PEMAHAMAN KONSEP FISIKA MATERI ALAT OPTIK PADA SISWA SMA KELAS X PEMINATAN IPS - Istiawan, Rahmat; Mosik, Mosik; Sopyan, Achmad (UPEJ Unnes Physics Education Journal, 2016)
In this research developed a media-assisted learning in the form of a mind map applications Prezi as a learning support materials physics in optical devices for high school students specialization social class. Media products produced in the form of mind map that can be accessed online through smart phones and tested in three groups of respondents based on the lines of inquiry that lecturers, teachers, and students. The media implementation to the respondent aims to determine the validity of the media, media practicality and increase student understanding after using the media. From the test results obtained validity media value of 4.24 categorized as very feasible to use as a learning support material physics in optical devices. Results practicality in using media obtained percentage value of 86.153% with the category of practical use. While student learning scores after using instructional media there is value gain of 0.416. Based on the results of this study concluded that the learning media can improve the understanding of the concept of students with moderate learning outcome categories.